STUDY OF FAST PATROL BOAT MODELS WITH AND WITHOUT TUNNELS ON THE EFFECT OF RESISTANCE USING COMPUTATIONAL FLUID DYNAMICS - S, Sutiyo; Munazid, Ali; Poundra, Gde A. Prabhawatya; Suwasono, Bagiyo (Journal of Marine-Earth Science and Technology, 2023)
Indonesia as an archipelago countries demand modern boats for marine security, resulting in a surge in the development of past patrol vessels. The investigation in this study focused on designs with and without a tunnel at the bottom to determine which design provided the least resistance. CFD offer realistic findings for comparing the problems encountered by two distinct kinds of fast patrol boats. The computation the use of no tunnel, the use of a tunnel on fast patrol boat reduced resistance by an average of 5.4%. According to the results of the CFD simulations, using a tunnel may greatly reduce the high pressure at the bottom in interactions with the flow of water. The utilization of using tunnel is a solution that may be employed more successfully for fast patrol boat operation